2017
DOI: 10.3892/or.2017.5602
|View full text |Cite
|
Sign up to set email alerts
|

CENP-H regulates the cell growth of human hepatocellular carcinoma cells through the mitochondrial apoptotic pathway

Abstract: Abstract. The genomic alterations of hepatocellular carcinoma (HCC) are still unclear. Centromere protein-H (CENP-H) has been shown to be associated with many solid tumors. Our previous study found that CENP-H was upregulated in HCC and was related to patient prognosis. However, the biological functions of CENP-H in HCC and the possible underlying mechanisms have not been well elucidated. In the present study, we demonstrated that CENP-H knockdown inhibited the proliferation of Hep3B cells and decreased colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Centromere protein A (CENPA) is one of the first identified kinetochore components in humans and is involved in several human malignancies 1114. It has been found that several centromere proteins were upregulated in HCC and associated with HCC malignant progression 11,15,16. Centromere protein K (CENPK) is important for proper kinetochore function and mitotic progression 17.…”
Section: Introductionmentioning
confidence: 99%
“…Centromere protein A (CENPA) is one of the first identified kinetochore components in humans and is involved in several human malignancies 1114. It has been found that several centromere proteins were upregulated in HCC and associated with HCC malignant progression 11,15,16. Centromere protein K (CENPK) is important for proper kinetochore function and mitotic progression 17.…”
Section: Introductionmentioning
confidence: 99%
“…Centromere protein H (CENP-H) is a component of the kinetochore and plays an essential role in mitotic processes ( Lu et al, 2017 ), accurate chromosome segregation ( Zhu et al, 2015 ) as well as appropriate kinetochore assembly ( Zhao et al, 2012 ). Many studies have shown that CENPH is closely associated with human cancers, including colorectal cancer ( Wu et al, 2017 ), renal cell carcinoma ( Wu et al, 2015 ), non-small cell lung cancer ( Liao et al, 2009 ) as well as breast cancer ( Walian, Hang & Mao, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Centromere protein H (CENP-H) is a component of the kinetochore and plays an essential role in mitotic processes (Lu et al 2017), accurate chromosome segregation (Zhu et al 2015) as well as appropriate kinetochore assembly (Zhao et al 2012). Many studies have shown that CENPH is closely associated with human cancers, including colorectal cancer (Wu et al 2017), renal cell carcinoma (Wu et al 2015), non-small cell lung cancer (Liao et al 2009) as well as breast cancer (Walian et al 2016).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%